2001
DOI: 10.1309/42u5-q2ev-rcbm-wpgj
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus–16 E6 Variants in Cervical Squamous Intraepithelial Lesions From HIV-Negative and HIV-Positive Women

Abstract: We studied 48 human papillomavirus (HPV)-16-positive squamous intraepithelial lesions (SILs) from HIV-negative patients (16 low-grade SILs [LSILs]; 32 high-grade SILs [HSILs]) and 13 HPV-16-positive SILs from HIV-positive patients with AIDS (1 LSIL; 12 HSILs). After HPV typing, the entire HPV-16 E6 coding region was amplified and sequenced in all samples. We detected 12 HPV-16 E6 prototypes and 4 variants among the LSILs in HIV-negative patients, and 15 HPV-16 E6 prototypes and 17 HPV-16 variants in the HSIL g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…These small studies have reported conflicting results regarding the effects of HIV coinfection on the distribution of HPV variants and the studied region (7). Icenogle et al (15), in Africa, and Perez-Gallego et al (24), in Spain, had similar results and did not observe any difference in the prevalence of European variants by HIV status.…”
Section: Gheit Et Almentioning
confidence: 68%
See 3 more Smart Citations
“…These small studies have reported conflicting results regarding the effects of HIV coinfection on the distribution of HPV variants and the studied region (7). Icenogle et al (15), in Africa, and Perez-Gallego et al (24), in Spain, had similar results and did not observe any difference in the prevalence of European variants by HIV status.…”
Section: Gheit Et Almentioning
confidence: 68%
“…HPV16 variants were more frequent than the prototype in all published studies concerning cervical carcinoma, although the prevalence of variants differs among geographic regions. The distribution of the HPV16 E6 European prototype has been described as being present in 9-47% of cervical cancer (21,35,38,39) and in 44-62% of high-grade lesions (18,21,24,39). European variants were described in 15-65% of cervical cancer (21,35,38,39) and in 24-37% of HSIL (18,21,24,39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, highly oncogenic HPV16 and 18 variants might be expected to have a particularly aggressive natural history in the presence of diminished host immune status, such as in HIV-positive women [5][6][7][8]. Women with human immunodeficiency virus (HIV)/ AIDS are at elevated risk of cervical cancer, as shown by studies of population-based US AIDS and cancer registries [9,10].…”
Section: Introductionmentioning
confidence: 99%